1980
DOI: 10.1507/endocrj1954.27.471
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal changes in serum concentrations of triiodothyronine and reverse triiodothyronine between summer and winter in normal adult men.

Abstract: Serum concentrations of thyroxine (T4), 3, 5, 3'-triiodothyronine (T3), 3, 3', 5'-triiodothyronine (reverse T3, rT3), thyronine-binding globulin (TBG), thyroid stimulating hormone (TSH) and cortisol in summer and in winter were compared in carefully selected normal adult men (aged 30-49 yr); 107 people from Sapporo (58 in summer and 49 in winter) and 15 hospital workers.A modest but significantly higher serum T3 concentration was recorded in winter than in summer, while T4, TSH, TBG and cortisol levels were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…They concluded that this indirectly reflected an increased serum level of T4. However, in contrast to this and in agreement with our data, other investigators have shown no change in serum T4 in euthyroid or hypothyroid subjects during seasonal exposure (Konno, 1980;Konno & Morikawa, 1982). In a continuously high altitude and cold exposed mountaineering group, Mordes et al. (1 983) demonstrated higher levels of serum total T4, free T4 and free T4 index compared to control vaiues.…”
Section: Discussionsupporting
confidence: 89%
“…They concluded that this indirectly reflected an increased serum level of T4. However, in contrast to this and in agreement with our data, other investigators have shown no change in serum T4 in euthyroid or hypothyroid subjects during seasonal exposure (Konno, 1980;Konno & Morikawa, 1982). In a continuously high altitude and cold exposed mountaineering group, Mordes et al. (1 983) demonstrated higher levels of serum total T4, free T4 and free T4 index compared to control vaiues.…”
Section: Discussionsupporting
confidence: 89%
“…This discrepancy in TSH regulation between the previous reports and our study may be because the adequacy of therapy was established by normal TSH response to TRH administration in this study rather than normalization of basal TSH alone. This finding is consistent with previous reports of lack of seasonal variation in TSH response to TRH administration in normal subjects (Konno, 1978;Konno, 1980).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we observed steady TSH and thyroid hormone values in euthyroid subjects during different months of the year. Even after comparing the coldest (December to March) to the hottest (June to September) months of the year, no significant change in TSH and thyroid hormone median values was observed except for a small increase in FT3 values (+2.9%, P <.01, Table ) during winter, an observation already reported in other temperate climate areas . Whether this is the consequence of increased thyroid gland T3 production or increased peripheral T4 to T3 conversion during the cold season is not clear …”
Section: Discussionmentioning
confidence: 75%